Aklimatisasi Anggrek Dendrobium Tiara Beauty >< Imelda Marina Dengan Perlakuan Konsntrasi Pupuk Nano Nutrien Dan AB Mix - Irawan (Indoensia), Iksan Yuda; Wahyudiningsih (Indoensia), Tri Suwarni; Jannah (Indoensia), Eka Nur (JURNAL VIGOR, 2023)
Research is about Acclimatization of Dendrobium Tiara Beauty’s Orchid Imelda Marina to nano nutrient and AB mix fertilizer concentration was carried out from June to July 2022 at the Nambangan Orchid Garden, Sidomulyo Village, Candimulyo District, Mageang Regency, Central Java. The research method used a factorial experiment (5x2) arranged in a complete randomized lock design with 4 blocks. The first factor is the type of fertilizer (P) including P1 = AB mix fertilizer P2 = nano nutrients fertilizer while the second factor is the fertilizer concentration (C) with a level of D0 = 0 ml/l, D1 = 0,5ml/l, D3 = 1,5 ml/l, D4 = 2,0 ml/l. The type of fertilizer has a significant effect on the increase in the number of leaves, leaf width, increase in stm height, leaf length, addition of stem diameter, and addition of new shoots but has no effect on the chlorophyll cntent parameter. The concentration of fertilizer has a significat effect on the parameters of the addition of stem diameter, addition of stem height, leaf length, addition of new shoots. Concentration of 1-2 ml/l gave the best rsults on the parameters of stem height, leaf length, addition of stem diameter and addition of new shoos of Dendroium orchids. The interaction vetween the type of fertilizer and the concentration of fertilizer has a significant effect on the addition of stem diameter and the parametes of incresiang stem height. Keywords: Dendrobium orvhids, concentration of fertilizers and types of fertilizers.